The great replacement narrative: fear, anxiety and loathing across the West - Sedgwick, Mark (Politics, religion & ideology, 2024)
The narrative of a coming ‘great replacement’ of long-established European populations by Muslim migrants and their offspring is one of the most widely believed and influential stories being told today by right-wing populists. It is often seen as a marginal conspiracy theory that has somehow become mainstream. In fact, as this article shows, it is neither marginal nor a conspiracy theory, but rather owes more to scholars such as Samuel Huntington than to the extreme Right. Extremists have indeed subsequently adopted the theory, sometimes adding conspiracies to it, but this is an addition to the basic theory, not part of it. As used by politicians, conspiracies are far from central. There are several explanations of the wide popularity of the theory, chief among which, it is suggested, is the fact that it is not a conspiracy theory. After this comes the mistaken idea that figures never lie.